Influence of different levels of dissolved oxygen on the success of Greenland halibut (Reinhardtius hippoglossoides) egg hatching and embryonic development - Mejri, Sahar; Tremblay, Réjean; Lambert, Yvan; Audet, Céline (Marine Biology, 2012)
The aim of this study was to determine the influence of different levels of dissolved oxygen (DO) on embryonic development (ED) and hatching success of Greenland halibut (Reinhardtius hippoglossoides) eggs. Fertilized eggs from six females were exposed to five DO levels: severely hypoxic (10 and 20 %sat [percent saturation]), moderately hypoxic (35 and 50 %sat), and normoxic (100 %sat). Greenland halibut eggs were highly tolerant to hypoxia, with hatching occurring at levels as low as 20 %sat. In severely hypoxic conditions (10 %sat), ED was impaired and no hatching occurred. Lipid composition, during ED, changed as a function of female origin and DO levels. Phospholipids were the dominant lipid class in eggs. Although triacylglycerols were a minor lipid class in terms of abundance, they were only used under severe hypoxia. The results suggest that severe hypoxia (between 10 and 20 %sat) has detrimental effect on the early development of Greenland halibut and may result in reduced recruitment and lower population abundance if the decreasing trend in the DO levels observed in the bottom waters of the Gulf of St. Lawrence continues in the future. Other species that share similar life histories may also be at risk. -- Keywords : Dissolve Oxygen Embryonic Development Lipid Class Hatching Success Severe Hypoxia.